2015
DOI: 10.4301/s1807-177520160002000005
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of Brazilian Internet Users and Its Impacts on the Use of Electronic Government Services

Abstract: The media relations make possible new structural arrangements regarding the constructions of identities and new paradigms relating to ethical and moral assumptions. Psychic formation processes are influenced by several variables that are interrelated in an open system, converging in anthropological, environmental, genetic, psychological, historical and social factors that determine relational interaction behaviors. However, in virtual cities where flow-image, timelessness and non-place reign, they enable new p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Concurrently, Brazil has experienced a rapid increase in the number of private medical schools, with considerable discrepancies in teaching-learning methods and quality-standard maintenance between public and private schools, as assessed by the National Examination of Students' Performance (ENADE) (Scheffer and Dal Poz, 2015;Antunes Dos Santos and Nunes, 2019). In addition, Brazil maintains immense socioeconomic inequalities that reflect upon the households with Internet access: extremely high in the upper social classes (A and B) and much lower in C, D, and E social classes (Araujo and Reinhard, 2016;UNESCO, 2019). Therefore, in developing countries, such as Brazil, online laboratory platforms are still in the process of implementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrently, Brazil has experienced a rapid increase in the number of private medical schools, with considerable discrepancies in teaching-learning methods and quality-standard maintenance between public and private schools, as assessed by the National Examination of Students' Performance (ENADE) (Scheffer and Dal Poz, 2015;Antunes Dos Santos and Nunes, 2019). In addition, Brazil maintains immense socioeconomic inequalities that reflect upon the households with Internet access: extremely high in the upper social classes (A and B) and much lower in C, D, and E social classes (Araujo and Reinhard, 2016;UNESCO, 2019). Therefore, in developing countries, such as Brazil, online laboratory platforms are still in the process of implementation.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial concern of this study was to assess whether the tool accessibility would be similar, in the context of the social diversity that is found in Brazil (Araujo and Reinhard, 2016;UNESCO, 2019). Despite socioeconomic differences, the results obtained have shown that most of the students had access to the Internet and computers outside the RPMS campus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation